1977
DOI: 10.1037/0278-7393.3.4.357
|View full text |Cite
|
Sign up to set email alerts
|

Constructive processes in linear order problems revealed by sentence study times.

Abstract: The time spent studying sentences that described the pairwise relations comprising linear orders to be constructed was measured. The results were consistent with the theory of constructive processes described earlier by Foos, Smith, Sabol, and Mynatt, except when the first two relations presented had no elements in common. In this situation, subjects were shown to possess two strategies for representing the order information in memory, depending on the form and content of the sentences. When the elements of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
0

Year Published

1981
1981
2003
2003

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 14 publications
(40 reference statements)
3
29
0
Order By: Relevance
“…Previous research (e.g., Mynatt & Smith, 1977;Oakhill & Johnson-Laird, 1984;Potts, 1972) has shown that reasoning performance is better when the premises are presented in a continuous order (e.g., AB, BC, CD) than when they are presented in a discontinuous (e.g., AB, CD, BC) or in a semi-continuous order (e.g., BC, CD, AB) (but see Ehrlich & Johnson-Laird, 1982). For the discontinuous order, this is due to the fact that up to a certain point (in the example: up to the second premise), no integrated representation can be constructed (e.g., Potts, 1972).…”
Section: Methodsmentioning
confidence: 98%
See 3 more Smart Citations
“…Previous research (e.g., Mynatt & Smith, 1977;Oakhill & Johnson-Laird, 1984;Potts, 1972) has shown that reasoning performance is better when the premises are presented in a continuous order (e.g., AB, BC, CD) than when they are presented in a discontinuous (e.g., AB, CD, BC) or in a semi-continuous order (e.g., BC, CD, AB) (but see Ehrlich & Johnson-Laird, 1982). For the discontinuous order, this is due to the fact that up to a certain point (in the example: up to the second premise), no integrated representation can be constructed (e.g., Potts, 1972).…”
Section: Methodsmentioning
confidence: 98%
“…All problems consisted of five premises, linking six objects/ subjects with the temporal relation "before" (constant sentence frame, Mynatt & Smith, 1977). The premises were isotropic: the second term of each premise reoccurred as the first term in the next premise.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Performance is affected by the order in which information is presented (Foos, Smith, Sabol, & Mynatt, 1976), the strategy that participants adopt in representing presented information (Mynatt & Smith, 1977), the completeness of the underlying ordering (Foos, 1980), the number of items in the ordering (Foos, 1980), the relationship between a sentence adjective and an item's placement (Potts & Scholz, 1975), and various combinations of the above (Foos, 1980). The present paper examines the effects produced by presentation order in an attempt to determine whether these effects can be attributed to the need for different processing for different inputs or simply to differences in the amount of information that must be held in store pending recall.…”
mentioning
confidence: 99%